2020
DOI: 10.1177/0300060520950563
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL17A in endometrial carcinoma and effects of IL17A on biological behaviour in Ishikawa cells

Abstract: Objective A growing body of evidence suggests chronic inflammation triggers the process of endometrial carcinogenesis. Interleukin (IL) 17A is an important proinflammatory factor involved in the tumour angiogenesis processes of many solid tumours. This study aimed to characterize the function of IL17A in endometrioid-type endometrial carcinoma. Methods Levels of IL17A in human endometrial tissues were analysed by immunohistochemistry. In vitro proliferation and migration were analysed in Ishikawa cells treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Ning et al (111) suggested that IL-17A may not promote the cell growth directly but could have a vital effect on HEC-1A cells proliferation mediated by CD68 + CD163 + macrophages. However, the latest study by Cheng et al (82) confirmed the promoting effect of IL-17A on Ishikawa cells proliferation. The discrepancy among these studies may attribute to the differentiation grade and hormone receptor expression of cancer cells.…”
Section: Regulating Cell Proliferation and Growthmentioning
confidence: 96%
See 4 more Smart Citations
“…Ning et al (111) suggested that IL-17A may not promote the cell growth directly but could have a vital effect on HEC-1A cells proliferation mediated by CD68 + CD163 + macrophages. However, the latest study by Cheng et al (82) confirmed the promoting effect of IL-17A on Ishikawa cells proliferation. The discrepancy among these studies may attribute to the differentiation grade and hormone receptor expression of cancer cells.…”
Section: Regulating Cell Proliferation and Growthmentioning
confidence: 96%
“…However, the latest study by Cheng et al. ( 82 ) confirmed the promoting effect of IL-17A on Ishikawa cells proliferation. The discrepancy among these studies may attribute to the differentiation grade and hormone receptor expression of cancer cells.…”
Section: Roles Of Interleukins In Ecmentioning
confidence: 96%
See 3 more Smart Citations